Penggunaan Media Sosial sebagai Preferensi Dakwah pada Organisasi Persatuan Keluarga Alumni Timur Tengah Mandailing Natal - Ahmad Alpin Sahri; Datuk Imam Marzuki; Siti Rahma Harahap (YASIN, 2026)
Although digital dakwah (Islamic preaching) via social media has been widely studied, research that specifically examines preferences in selecting social media platforms as dakwah strategies within Middle Eastern alumni organizations remains limited. This study aimed to analyze the use of social media as a preferred dakwah medium and to identify the reasons underlying platform selection by the Organisasi Persatuan Keluarga Alumni Timur Tengah Mandailing Natal (POKATT). A qualitative approach with a descriptive design was employed, involving six key informants purposively selected from the organization’s leadership. Data were collected through observation, in-depth interviews, and documentation, and were analyzed descriptively through data reduction, data display, and conclusion drawing, with validity ensured by source triangulation. The findings show that WhatsApp, Instagram, and Facebook are actively and synergistically utilized as digital dakwah channels: WhatsApp is used for internal discussions and distribution of study materials, Instagram for presenting visually engaging and educational content targeting young audiences, and Facebook for publishing more in-depth dakwah content and live broadcasts. Preferences for these platforms are based on considerations of effectiveness, ease of access, broad reach, low cost, and their capacity to convey dakwah messages creatively and interactively. These findings reinforce the relevance of Uses and Gratifications Theory, whereby both audiences and preachers play an active role in selecting media that align with their dakwah needs. The study concludes that digital literacy and contextual dakwah communication strategies are crucial to maintaining the authenticity of Islamic messages in the digital era and recommends that dakwah organizations optimize the planned and responsible use of social media.